Average evolution and size-topology relations for coarsening 2d dry foams - Chieco, Anthony T.; Sethna, James P.; Durian, Douglas J. (Frontiers in Soft Matter, 2022)
Two-dimensional dry foams coarsen according to the von~Neumann law as dA/dt ~ (n-6) where n is the number of sides of a bubble with area $A$. Such foams reach a self-similar scaling state where area and side-number distributions are stationary. Combining self-similarity with the von~Neumann law, we derive time derivatives of moments of the bubble area distribution and a relation connecting area moments with averages of the side-number distribution that are weighted by powers of bubble area. To test these predictions, we collect and analyze high precision image data for a large number of bubbles squashed between parallel acrylic plates and allowed to coarsen into the self-similar scaling state. We find good agreement for moments ranging from two to twenty.